Fulfillment Of The Rights To Basic Education In Ambon City During The Covid-19 Pandemic - Lucia Charlota Octovina Tahamata; Welly Angela Riry (Faculty of Law, Universitas Pattimura, 2021)
Fulfilling of the Right to Education is a part of Human Rights. The right to education has become important in line with government policies to work from home during the Covid 19 pandemic. During the Covid-19 pandemic the learning process uses two learning methods, namely the online method and the offline method. Two learning methods are used for learning but the process has not been implemented optimally by both teachers and students, there are always obstacles faced. The purpose of this study was to determine and study the fulfillment of the right to basic education during the Covid 19 pandemic. The authors conducted research at the Department of Education and Culture of Elementary Schools and Junior High Schools in Ambon City using empirical research methods, data collection techniques through interviews and observations to students. Based on the results of the research conducted, the authors found that the distance learning system in schools in Ambon City was not optimal due to facilities and infrastructure and mastery of technology. which is still low. Fulfilling the right to education requires the involvement of all parties, namely the government, educators, students and parents to work together in the teaching and learning process during the Covid-19 pandemic. The government, educators, students and educational administering institutions at a practical level must strive to develop learning methods with good digital literacy skills so that they need to be improved through trainings using media for online learning for both educators, students and parents